2018
DOI: 10.5897/ajb2018.16641
|View full text |Cite
|
Sign up to set email alerts
|

Preliminary study on rice straw degradation using microbial inoculant under shake flask condition

Abstract: Abundance and unmanaged agriculture residues lead to unutilized resource waste and environmental pollution. Application of microbial technology to manage agriculture waste could produce value-added product. A preliminary study on biodegradation of rice straw using different potential microorganisms was tested under controlled environment. Three different inoculant cultures were used to observe their efficiency in rice straw degradation. Combination cultures microorganisms coding AMB1 shows the potential degrad… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(2 citation statements)
references
References 14 publications
(12 reference statements)
0
1
0
Order By: Relevance
“…It was found that of all these three test species Penicillium chrysogenum was highly active followed by Aspergillus flavus and A. oryzae in degradation of rice straw under field conditions (Table 2) but when these were used as mixed inoculants the degradation of rice straw fastened synergistically and the highest rate of decomposition was recorded with mixed cultures of all three species of Penicillium chrysogenum, Aspergillus flavus and A. oryzae that degraded approximately 75% of the rice straw under field conditions while only approx. 20% of the heat killed treated rice straw (control) was degraded under similar conditions of incubation (Table 2) [38,39,40]. The endophyte fungus Chaetomium globosum DX-THS3 has been reported to produce lignocellulolytic enzymes and glycyrrhizic acid 3-O-mono-D-glucuronide under SSF conditions utilizing licorice straw as substrate that is able to degrade the lignocarbohydrates [41].…”
Section: Resultsmentioning
confidence: 96%
“…It was found that of all these three test species Penicillium chrysogenum was highly active followed by Aspergillus flavus and A. oryzae in degradation of rice straw under field conditions (Table 2) but when these were used as mixed inoculants the degradation of rice straw fastened synergistically and the highest rate of decomposition was recorded with mixed cultures of all three species of Penicillium chrysogenum, Aspergillus flavus and A. oryzae that degraded approximately 75% of the rice straw under field conditions while only approx. 20% of the heat killed treated rice straw (control) was degraded under similar conditions of incubation (Table 2) [38,39,40]. The endophyte fungus Chaetomium globosum DX-THS3 has been reported to produce lignocellulolytic enzymes and glycyrrhizic acid 3-O-mono-D-glucuronide under SSF conditions utilizing licorice straw as substrate that is able to degrade the lignocarbohydrates [41].…”
Section: Resultsmentioning
confidence: 96%
“…YAO et al (5) stated that the fulvic acid (FA) and humic acid (HA)) especially humic acid, decreased the release of Pb, Cu and Cd, reducible and oxidable Pb, Cu and Cd, so, humic and fulvic are promising tools for immobilize heavy metals and prevent it from absorption. Nurul et al (6) suggested that the combination culture of microorganisms have a vital role for biodegradation of rice straw and faster of composting process. Also, these groups of microorganisms have ability of to enhance final product so, using combination culture decrease period of process and used to manage agriculture waste.…”
Section: Introductionmentioning
confidence: 99%